Analysis and verification of safety computer time constraints for train-to-train communications - Ying GAO; Yuan CAO; Yongkui SUN; Lianchuan MA; Chunhua HONG; Yuzhuo ZHANG (Tongxin xuebao)
In order to adapt to the development trend of the communication based train control (CBTC) system from train-ground communication mode to train-to-train communication mode, a verification approach for time constraints of multi-period applications concurrence on-board safety computer based on time Petri net was proposed. By taking the double 2 out of 2 on-board safety computer as an example, the multi-period applications concurrence nature of the safety computer was analyzed. Time Petri net (TPN) was utilized to calculate the time schedulable interval. Then several cases were analyzed based on the inference of this approach. The analysis and verification results indicate that onboard safety computer can meet the time constraints of more than three periodic safety-critical applications under the condition of single-core with main frequency of 1GHz, which demonstrates the effectiveness of verifying and evaluating the time constraints of safety computer periodic applications using TPN.